Selection of the intrinsic polarization properties of animal optical materials creates enhanced structural reflectivity and camouflage. (5th July 2017) - Feller, Kathryn D.; Jordan, Thomas M.; Wilby, David; Roberts, Nicholas W.
Abstract : Many animals use structural coloration to create bright and conspicuous visual signals. Selection of the size and shape of the optical structures animals use defines both the colour and intensity of the light reflected. The material used to create these reflectors is also important; however, animals are restricted to a limited number of materials: commonly chitin, guanine and the protein, reflectin. In this work we highlight that a particular set of material properties can also be under selection in order to increase the optical functionality of structural reflectors. Specifically, polarization properties, such as birefringence (the difference between the refractive indices of a material) and chirality (which relates to molecular asymmetry) are both under selection to create enhanced structural reflectivity. We demonstrate that the structural coloration of the gold beetle Chrysina resplendens and silvery reflective sides of the Atlantic herring, Clupea harengus are two examples of this phenomenon. Importantly, these polarization properties are not selected to control the polarization of the reflected light as a source of visual information per se. Instead, by creating higher levels of reflectivity than are otherwise possible, such internal polarization properties improve intensity-matching camouflage. This article is part of the themed issue 'Animal coloration: production, perception, function and application'.